The effect of tax treaties on market based finance: Evidence using firm-level data - Ronald B. Davies; Neill Killeen (University College Dublin, UCD School of Economics, 2018)
Tax arbitrage is often cited as a potential motive for the substantial growth and complexity of market based finance. Tax treaties are an important feature of the international tax system and can be used to reduce the tax burden on cross-border capital flows. Using an EU firm-level dataset and a number of alternative tax treaty measures, this paper investigates the importance of tax treaties on the investment decisions of a large sample of non-bank financial institutions. The novel dataset includes conduits such as special purpose entities which are often used to channel cross-border investments. Our results show that tax treaties influence the extensive margin of non-bank financial FDI with conduit related investments particularly sensitive to international taxation.
Keywords: F23; F65; G23; G32; 330; Tax treaties; market-based finance; shadow banking system; conditional logit model; mixed logit model; nested logit model